1998
DOI: 10.1042/bj3320127
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal antibody catalytic variability

Abstract: We have performed a systematic variability study of polyclonal antibody catalysis by using five rabbits immunized with the same hapten. Important results from this work are the following. (1) Similarities were observed in the catalytic polyclonal antibodies derived from all five rabbits. Four of the five rabbits produced polyclonal samples that were nearly the same in terms of catalytic activity, whereas the fifth rabbit, designated as rabbit 2, displayed a somewhat higher level of catalytic activity. The cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
1
3
0
1
Order By: Relevance
“…To obtain the serum, all of these blood samples were left at room temperature (22 °C) for 30 min and then centrifuged at 1191× g for 10 min, after which the supernatant was collected. In accordance with a previous report [ 17 ], antibody titers in these sera were confirmed by direct ELISA. For the present study, we ensured the collection of sufficient antibody titers, as the results of ELISA performed with 40,000-fold diluted serum after 5 times immunization had previously shown absorbance values of 1.5–2.0 at 450 nm/630 nm wavelengths.…”
Section: Methodssupporting
confidence: 92%
“…To obtain the serum, all of these blood samples were left at room temperature (22 °C) for 30 min and then centrifuged at 1191× g for 10 min, after which the supernatant was collected. In accordance with a previous report [ 17 ], antibody titers in these sera were confirmed by direct ELISA. For the present study, we ensured the collection of sufficient antibody titers, as the results of ELISA performed with 40,000-fold diluted serum after 5 times immunization had previously shown absorbance values of 1.5–2.0 at 450 nm/630 nm wavelengths.…”
Section: Methodssupporting
confidence: 92%
“…Both anxieties have been shown to be without foundation. Thus, as far as the first is concerned, catalysis by all of the polyclonal IgG preparations investigated to date in different laboratories has not deviated from single-site (Michaelis-Menten) saturation kinetics (e.g [2][3][4][10][11][12][13][14][15][16][17][18]). Given the heterogeneous nature of the polyclonal antisera, this observation may be regarded as counter-intuitive.…”
Section: Improvement In Hydrolytic Antibody Activity By Change In Hapmentioning
confidence: 99%
“…This approach avoids the problematic immune responses associated with monoclonal catalytic antibodies. Several studies have demonstrated that PCAbs active in itro can be generated relatively simply, rapidly and cheaply [10][11][12][13][14]. Here, we provide the first evidence that enzymically active PCAbs can be useful as therapeutic reagents in i o.…”
Section: Introductionmentioning
confidence: 57%
“…Furthermore, this strategy can be used for treatment of enzyme deficiencies and cardiovascular diseases. Although the catalytic activity of PCAbs generated in past studies was modest [10,13], improvements in hapten design methods and immunization strategies may lead to an increase in the catalytic activity of antibodies and broaden the application of catalytic antibodies for therapeutic strategies in i o.…”
Section: Discussionmentioning
confidence: 99%